Food consumption and coping strategy of local community facing the climate change issue - Muh. Fadli; Ikawati Karim; Rahmaniah HM; Chumphon Angkananon (Agribusiness Department, Agriculture and Forestry Faculty, Universitas Sulawesi Barat, Indonesia, 2025)
The quality of a human's life is influenced by the nutrients they consume. In line with this statement, climate change, such as extreme rainfall or prolonged dry seasons, impacts crop yields and agricultural productivity. It is suspected that this will change food consumption levels because it affects local food availability and community income from agricultural products. This study aims to determine the level of food consumption and the adaptation strategies in the Research area, Polewali Mandar Regency, West Sulawesi, Indonesia. The analysis used the Food Consumption Score (FCS) and the Coping Strategy Index (CSI). The results show that all households have a FCS in the high category, with an average value of 81. Despite this, food consumption is still dominated by cereals, especially rice, and animal protein sources such as fish, while other food groups, such as fruits, nuts, and dairy products, are still low in frequency. The most common CSI for the local community in the midst of climate change issues is reducing food consumption, replacing food with cheaper alternatives, borrowing food from family and relatives, and taking on additional work. Another strategy is for the local community to encourage family members to work outside the community.